Engineering effective structural defects of metal–organic frameworks to enhance their catalytic performances. Issue 8 (13th February 2020) - Wang, Jianjian; Liu, Lingmei; Chen, Cailing; Dong, Xinglong; Wang, Qin; Alfilfil, Lujain; AlAlouni, Mohammed R.; Yao, Kexin; Huang, Jianfeng; Zhang, Daliang; Han, Yu
Abstract : Creation of more effective open metal sites via individual tuning of missing-linker or missing-cluster defects greatly enhances their catalytic performance. Abstract : Metal–organic frameworks (MOFs) with a high density of metal nodes have great potential in the application of heterogeneous catalysis. However, identifying the real active site in MOF structures and tuning its amount to further improve its catalytic performance are still a great challenge. In this paper, defective UiO-66 modulated with trifluoroacetic acid (TFA) was synthesized and used for the conversion of cyclohexanone to cyclohexanol via hydrogen transfer. We found that not all structural defects were responsible for catalytic reaction, and only structural defects where open metal sites are created by a modulator were effective for cyclohexanone conversion. Then we successfully tuned the number of each type of effective structural defect (that is, missing-cluster defects or missing-linker defects) in modulated UiO-66 via precise control of the synthetic/treatment conditions. Our experimental results showed that the creation of both types of structural defects can increase the amount of effective open metal sites and then enhance their catalytic performances under the same conditions. Furthermore, the mechanism study confirmed that this reaction indeed proceeded on effective open metal sites. Our findings have further deepened the understanding of the roles of structural defects in MOF heterogeneous catalysis.